Zooplancton del Domo de Costa Rica: taxonomía y biogeografia - Vicencio Aguilar, Maricela E (1996)
A list of the species and taxa of sorne pelagic animals from a tropical upwelling region, based on collections made off the coast of Costa Rica is presented. The list includes a total of 224 species, 53 genera arid II subespecific forms in Cnidaria, Annelida, Mollusca, Artropoda (Crustacea), Chaetognatha and Pisces